Reexamining the timing of reindeer disappearance in southwestern France in the larger context of late glacial faunal turnover. (1st September 2016) - Costamagno, Sandrine; Barshay-Szmidt, Carolyn; Kuntz, Delphine; Laroulandie, Véronique; Pétillon, Jean-Marc; Boudadi-Maligne, Myriam; Langlais, Mathieu; Mallye, Jean-Baptiste; Chevallier, Aude
Abstract: During the Tardiglacial, the significant changes in plant communities relating to climate changes were responsible for faunal recompositions perceptible throughout Europe. In this article, by comparing all the AMS radiocarbon dates obtained on reindeer bone and the faunal communities derived from bone assemblages dated between ca. 19, 000 cal BP and 11, 700 cal BP, we examine the disappearance of reindeer from the southwest of France. The new dating shows that the species disappeared slightly earlier in the Pyrenees, at ca. 14, 000 cal BP, than in the northern Aquitaine where reindeer remained until ca. 13, 800 cal BP. In the southwest of France, the natural range of reindeer began to fragment very early, from the Bølling period, and by the end of the GI-1e only residual reindeer populations remained in the Dordogne. These results are consistent with those observed throughout the rest of France and Switzerland, where reindeer also disappeared at the GI-1e/GI-1ca transition. Further north (Belgium, Germany, and Denmark), the species found favourable conditions for its development throughout the GS-1. In England, reindeer remained present until the beginning of the Holocene at very low latitudes compared to what has been observed on the continent. These results clearly illustrate the gradual withdrawal of reindeer towards the north and east of Europe and probably the local extinction of reindeer in Britain.